Sunday

April 20, 2014

April 20, 2014

Posted by **Labz** on Monday, June 4, 2012 at 5:54pm.

- Math -
**Reiny**, Monday, June 4, 2012 at 7:02pmlet f(x) = x^3 - 4x^2 + x + 6

f(1) = 1-4+1+6 ≠0

f(-1) = -1 - 4 -1 + 6 = 0

so (x+1) is a factor

Using synthetic division or long algebraic division

x^3 - 4x^2 + x + 6

= (x+1)(x^2 - 5x + 6)

= (x+1)(x-6)(x+1)

so x = 6 or x = -1 (a double root at x=-1)

- Math -
**Labz**, Monday, June 4, 2012 at 7:07pmthank you!

**Related Questions**

BobPursley3...another one.. - Problem 3: 4x/(x+2) - 8/(x-1) What I did: Common ...

Pre-Calculus - How do you factor this completly 7x*(4x-5)^3+(4x-5)^4 I am ...

12th grade Math? - How would you factor 3x^3-4x^2+4x-1? P.S. Factor theorem does...

algebra2 - Solve each of the following quadratic equations. can some explain how...

math - solve the equation x^3-5x^2-4x+20=0 I need a hint on how to solve this ...

Calculus - relative extrema x^4-2x^2+5 so far I know how to find the derivative ...

algebra - How to factor 4x^3 -4x+16 ? how can i factor it when its missing the ^...

Simplifying Rational Expressions - 1. 4x-12/4x 2. d+7/d^2-49 3.t2-25/t^2+t20 4....

Simplifying Rational Expressions - 1.4x12 / 4x 2.d+7 / d^2-49 3.t^2-25 / t^2+t-...

math,help,factoring - i need help i don't know how to do the next step. factor ...